Sprint acceleration mechanical outputs: direct comparison between GPEXE Pro2 and 1080 Sprint devices - Komino, P.; Le Mat, Y.; Zadro, I.; Osgnach, C.; Morin, J. B. (Sport Performance & Science Reports, 2022)
Sprint force-velocity profiling is a simple and practical way to accurately assess the macroscopic propulsion capacities underlying players` sprint acceleration performance (1-3). Since this approach can be based on position- or speed-time data, many systems can be used depending on the context (e.g. radar, laser, timing gates or Global Positioning System (GPS) units) (4). It is thus important to study inter-device differences to inform about the magnitude of intra- and interdevice reliability. The increasing accuracy and popularity of GPS in team sport justifies the investigation of sprint forcevelocity main outcomes derived from speed-time data obtained with this technology (5). Our aim was to assess the differences between a specific model of GPS and a linear encoder training and testing device, and compare their inter-trial reliability.